More aonla in lesser area - Singh, A. K.; Singh, Sanjay; Joshi, H. K. (Indian Horticulture, 2019)
The plants were patch budded in 2002 on deshi rootstocks (in-situ) planted in 2001, following different planting systems using scion shoots of single genome plant of NA-7 variety of aonla. Flowering and fruiting took place during third year and the economic yield was realized from fifth year of budding which continued to increase the yield optimally up to tenth year. Among all planting systems, maximum yield (`220.09 q/ha) and net profit (`1,50,072/ha) was obtained in double hedgerow, showing 123.46 and 118.15 per cent more yield and profit, respectively over the traditionally recommended square system of planting under rainfed condition.